Morphology of RuO2(110) Films during Electrochemistry - Reese, Austin Jerad; Wadehra, Neha; Suntivich, Jin; Schlom, Darrell (Meeting abstracts (Electrochemical Society), 2023)
RuO2 is a well-known electrocatalyst for the oxygen evolution reaction (OER), a critical electrochemical reaction in the water electrolyzer. The behavior of RuO2 during the OER is, however, a subject of debate, in particular, the corrosion mechanism. In this contribution, we report an electrochemical AFM (EC-AFM) study on well-defined RuO2 films grown using molecular beam epitaxy (MBE). We track the morphology of step edges prior, during, and after the OER in acid and alkaline electrolytes to gain insights into the corrosion behavior. Our EC-AFM experiment shows the potential range of RuO2 corrosion and hints at the role of strain and defects in the RuO2 stability. The heterogeneity of corrosion will be discussed in the context of the catalyst longevity along with possible mitigation strategies.